To PARP or not to PARP?—Toward sensitizing acute myeloid leukemia stem cells to immunotherapy. (21st October 2019) - Heyman, Benjamin; Jamieson, Catriona
Abstract : A new study reveals that leukemia stem cells (LSCs) in acute myeloid leukemia downregulate natural killer cell‐activating receptor ligands to evade immune surveillance via the transcriptional co‐factor PARP1. The inhibition of PARP1 sensitizes LSCs to immunotherapy, highlighting its potential as a therapeutic target. Abstract : New research shows that leukemia stem cells evade immune surveillance by downregulating natural killer cell‐activating receptor ligands.